2009
DOI: 10.1021/jp906871g
|View full text |Cite
|
Sign up to set email alerts
|

Study of Adsorption of Aminobenzoic Acid Isomers on Silver Nanostructures by Surface-Enhanced Infrared Spectroscopy

Abstract: o-, m-, and p-aminobenzoic isomers were studied with surface-enhanced infrared absorption (SEIRA) spectroscopy and temperature-programmed desorption (TPD) on vacuum-evaporated silver films and on a silver powder. Each aminobenzoic acid (ABA) isomer was complexed with a silver ion(s) and modeled with density functional theory to aid in the interpretation of the SEIRA results. Atomic force microscopy and scanning electron microscopy compared and contrasted surface roughness between the evaporated silver film and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 35 publications
0
42
0
Order By: Relevance
“…1 SEIRA spectrum (bottom) of the 5 lL exposure of 4FBA adsorbed from n-pentane there is a band at 1397 cm À1 attributed to a COO stretching/ring deformation mode(s) from 4-fluorobenzoate ion (4FBI) formation in the monolayer. It is well known that benzoic acids ionize to benzoate ions at least in the monolayer during deposition on most transition metal surfaces [15][16][17][18][19][20]. The COO stretching band does not grow much in intensity as the amount of 4FBA deposited onto the silver film is increased in Fig.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…1 SEIRA spectrum (bottom) of the 5 lL exposure of 4FBA adsorbed from n-pentane there is a band at 1397 cm À1 attributed to a COO stretching/ring deformation mode(s) from 4-fluorobenzoate ion (4FBI) formation in the monolayer. It is well known that benzoic acids ionize to benzoate ions at least in the monolayer during deposition on most transition metal surfaces [15][16][17][18][19][20]. The COO stretching band does not grow much in intensity as the amount of 4FBA deposited onto the silver film is increased in Fig.…”
Section: Resultsmentioning
confidence: 98%
“…It has been previously demonstrated that a seven nanometer silver film as determined by the QCM is optimal for SEIRA [16]. Earlier scanning electron and atomic force microscopy studies have shown these silver films to be rough with an average particle size of 50-100 nm in diameter and an average particle height of about 5 nm [16,19]. Henceforth, the phrase a 'silver film' is with reference to seven nanometers of silver as determined by the QCM evaporated on a CaF 2 substrate.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many literatures reported the synthesis of resins based on hydrogen bonding [23][24][25], and adsorption mechanism on basis of hydrogen bonding is usually clarified by thermodynamic or theoretical calculation [26][27][28]. To the best of our knowledge, direct evidence to testify hydrogen bonding between the resin and the adsorbate is little discussed [29].…”
Section: Introductionmentioning
confidence: 99%